The Barcelona School of Ecological Economics and Political Ecology A Companion in Honour of Joan Martinez-Alier - Villamayor-Tomas, Sergio; Muradian, Roldan (Studies in Ecological Economics,, 2023)
In this open access book, ecological economics and political ecology traditions converge into a single academic school. The book constitutes a common ground where multiple and critical voices are expressed, covering a broad scope of urgent matters at the crossroad between society, economy and the natural environment. The manuscripts composing this compendium offer appealing material for both experienced and younger researchers interested in interdisciplinary exchanges in the field of the social environmental sciences. It combines historical accounts with recent theoretical and empirical developments revolving around the interaction between three foundational notions of the Barcelona School: social metabolism, environmental justice and self-reflective science.